Kiprah KH. Abu Dardiri (1895-1967) Dalam Perkembangan Muhammadiyah di Daerah Banyumas: Perkembangan Muhammadiyah di Kabupaten Banyumas, Riwayat Hidup KH. Abu Dardiri, Kiprah KH. Abu Dardiri Dalam Perkembangan Muhammadiyah di Daerah Banyumas - Valid Fathony, Bimba (Siginjai: Jurnal Sejarah, 2023)
This study aims to explain related to the Gait of KH. Abu Dardiri in the Development of Muhammadiyah in the Banyumas Region. The method used in studying the topics raised is the historical method based on heuristic stages, source criticism, interpretation, and historiography. In this article, the first point describes the development of Muhammadiyah in the Banyumas area, which consists of its initial establishment which lasted until 1940 and post-independence developments. In the next point explaining about KH. Abu Dardiri where he is a very influential figure in the history of the development of Muhammadiyah in the Banyumas area. He was Muhammadiyah consul for the Banyumas area before serving as Muhammadiyah consul he served as chairman of the Purbalingga branch of Muhammadiyah. Many of his actions have been felt to this day with various legacies and charitable efforts which are currently growing rapidly.